Temporal pattern and effect of COVID-19 on the trend of TB, DRTB, paediatrics TB and TB with HIV Coinfection: A decadal trend analysis - Pushpendra Bairwa; Mahesh C. Verma; Asha Kumari; Ajay Gupta; Yamini Singh (Journal of Family Medicine and Primary Care, 2024)
Background: India shares 2/3 of global TB burden. MDR and HIV coinfections are the main obstacle in achieving the successful TB control because it decrease the therapy effect. Objective: To analyze the long-term trends of incidence of tuberculosis cases and identify any differences between actual and projected cases after the COVID-19 pandemic. Methodology: A retrolective study was conducted in SMS medical college, Jaipur, and data were extracted from state TB cell and annual report published by central TB division. A multiplicative model was used for conducting time series analysis. The projected yearly number of cases were estimated using the line of best fit based on the least square method. Result: An increasing trend in the incidence of TB was observed, rising from 1,517,363 in 2008 to 2,404,815 in 2019. Similarly, DRTB also showed an increasing trend from 10,267 (0.67% of total new cases) in 2011 to 66,255 (2.75%) in 2019. The new cases of DRTB in 2020 were significantly lower than the projected number. The trend of HIV coinfection in TB cases fluctuated over the past decade. Conclusion: The findings reveal a concerning upward trajectory in TB incidence and DRTB cases over the decade. The fluctuating trend in HIV coinfection in TB cases emphasizes the complexity of addressing these interconnected health challenges.